Ordem Mundial no século XXI: uma reflexão a partir da cosmopolitização - Renata Maria Silva Ramos de Castro (2018)
The end of the Cold War brought irreversible changes in the way states relate. The decades since the fall of the Berlin Wall have been of intense adjustments in the way of life of national citizens, in the relationship between civilizations and in the flow of information, goods and people. The result is a society oriented to the present moment, anxious and intolerant. Thus, the purpose of this work is to present a series of reflections that culminate in the fundamental elements to the construction of the new world order based on cosmopolitan theory.